2012
DOI: 10.1083/jcb.201111079
|View full text |Cite
|
Sign up to set email alerts
|

TBC1D14 regulates autophagosome formation via Rab11- and ULK1-positive recycling endosomes

Abstract: The noncatalytic RabGAP protein TBC1D14 regulates the Rab11- and ULK1-positive recycling endosomes required for autophagosome formation upon starvation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
363
2
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 348 publications
(392 citation statements)
references
References 50 publications
26
363
2
1
Order By: Relevance
“…TBC1D14 is a RAB11 effector protein and is known to regulate autophagy and ATG9A trafficking via binding to the TRAPP complex 8, 11. It was found that proper ATG9A traffic between recycling endosomes and the Golgi apparatus depends on the generation of a tubular intermediate membrane compartment containing ATG9A, where a switch between RAB11 and RAB1 occurs and is facilitated by a TBC1D14‐TRAPPIII‐like complex.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…TBC1D14 is a RAB11 effector protein and is known to regulate autophagy and ATG9A trafficking via binding to the TRAPP complex 8, 11. It was found that proper ATG9A traffic between recycling endosomes and the Golgi apparatus depends on the generation of a tubular intermediate membrane compartment containing ATG9A, where a switch between RAB11 and RAB1 occurs and is facilitated by a TBC1D14‐TRAPPIII‐like complex.…”
Section: Resultsmentioning
confidence: 99%
“…DyLight‐680‐ and DyLight‐800‐conjugated secondary antibodies were obtained from Invitrogen (SA5‐10170 and SA5‐10044, 1:5,000). Antibodies used for immunofluorescence are as follows: mouse anti‐WIPI2 (from Sharon Tooze 40, 1:2,000), rabbit anti‐ATG16L1 (MBL, PM040, 1:200), hamster anti‐ATG9A (from Sharon Tooze 41, 1:1,000), rabbit anti‐ATG9A (Abcam, ab108338, 1:400), mouse anti‐myc (IF and WB—DSHB, cl9E10, 1:20), rabbit anti‐TBC1D14 (from Sharon Tooze 8, 1:200), chicken anti‐SNX18 (from Sven Carlsson, 26, 30, 1:200), goat anti‐myc (Abcam, ab9132, 1:500), mouse anti‐TfR (Santa Cruz Biotechnology, sc‐65877, 1:200), mouse anti‐Dynamin (Upstate/Millipore, 05‐319, 1:100). Alexa 488‐conjugated secondary antibodies were obtained from Invitrogen (A‐21206 and A‐21202, 1:500), and Cy3 and Cy5‐conjugated secondary antibodies were obtained from Jackson ImmunoResearch (Cy3: 715‐165‐151, 127‐165‐099 and 711‐165‐152, Cy5: 711‐495‐152 and 715‐175‐150).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although TBC1D14 has a putative RabGAP domain, it does not appear to have RabGAP activity for Rab11, instead it may act as a downstream effector of Rab11. Overexpression of TBC1D14 negatively regulates autophagy possibly by sequestering the ULK1 complex in the recycling endosome through the direct binding between TBC1D14 and ULK1 [86].…”
Section: The Plasma Membrane and Recycling Endosomesmentioning
confidence: 99%